Increased Platelet Distribution Width Is Associated With ST-Segment Elevation Myocardial Infarction and Thrombolysis Failure. (September 2014) - Cetin, Mustafa; Bakirci, Eftal Murat; Baysal, Erkan; Tasolar, Hakan; Balli, Mehmet; Cakici, Musa; Abus, Sabri; Akturk, Erdal; Ozgul, Sami
We investigated 2 hypotheses: (1) a relationship between platelet indices and stable coronary artery disease (CAD) and acute ST-segment elevation myocardial infarction (STEMI) and (2) a relationship between platelet indices on admission and thrombolysis outcomes in patients with STEMI. A total of 260 patients were enrolled. The white blood cell (WBC) and platelet distribution width (PDW) were found to be increased in patients with STEMI ( P for both < .001). White blood cell and PDW were independent predictors of acute STEMI. Mean platelet volume (MPV) and PDW were significantly higher in the thrombolysis failure group than in the thrombolysis success group (9.9 ± 1.8 vs 9.2 ± 1.5 fL, P = .021 and 17.7 ± 1.0 vs 16.4 ± 2.1 fL, P < .001, respectively). Mean platelet volume and PDW were independent predictors of thrombolysis failure. Patients with acute STEMI had higher PDW than did patients with stable CAD. In addition, higher PDW and MPV seem to correlate with thrombolysis failure in patients with STEMI.